Answer:
Step-by-step explanation:
<em>Complementary angles sum up to 90°</em>
<u>Given</u>
<u>Substituting P in the first equation</u>
- 2M + 3° + M = 90°
- 3M = 87°
- M = 29°
<u>Then </u>
Answer:
14
Step-by-step explanation:
Hypotenuse^2=base^2+perp^2
50^2=base^2+48^2
2500-2304=base^2
Base^2=196
Taking sq root
Base=14
Answer:
Step-by-step explanation:
Let's call hens h and ducks d. The first algebraic equation says that 6 hens (6h) plus (+) 1 duck (1d) cost (=) 40.
The second algebraic equations says that 4 hens (4h) plus (+) 3 ducks (3d) cost (=) 36.
The system is
6h + 1d = 40
4h + 3d = 36
The best way to go about this is to solve it by substitution since we have a 1d in the first equation. We will solve that equation for d since that makes the most sense algebraically. Doing that,
1d = 40 - 6h.
Now that we know what d equals, we can sub it into the second equation where we see a d. In order,
4h + 3d = 36 becomes
4h + 3(40 - 6h) = 36 and then simplify. By substituting into the second equation we eliminated one of the variables. You can only have 1 unknown in a single equation, and now we do!
4h + 120 - 18h = 36 and
-14h = -84 so
h = 6.
That means that each hen costs $6. Since the cost of a duck is found in the bold print equation above, we will sub in a 6 for h to solve for d:
1d = 40 - 6(6) and
d = 40 - 36 so
d = 4.
That means that each duck costs $4.
Are you tryna solve for x?